Lectotypification of the names of three species of Gentiana (Gentianaceae) occurring in India - Shabir, Mohd; Agnihotri, Priyanka; Husain, Danish; Tiwari, Jk.; Husain, Tariq (Phytotaxa, 2017)
During our ongoing revisionary studies of the genus Gentiana in India, we found that no lectotypes for the names G. elwesii C.B. Clarke, G. gilvostriata C. Marquand and G. listeri Burkill have been designated, which are here proposed.